(3TQM GddeY aj Yde GdMSGHs - (3CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,TgGH GdOjf, J (B815 (3g` s
(3ChdgG (B:s
(3gPG JYdjbg eNJUQ LYdJg JhVjMkG Ydi GdebOeI GdeSeGg HGddeY ai Yde GdMSGH JCdja GHf GdgGFe s
(3BNQgG (B:s
(3hEf TFJ aGfSH GdNeSI YTQ Edi GdSJjf hbO JeJ HYhf Gddg s
(3GdfSNI HgG MhGTs
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B226s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1562s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs